Study of pattern related to side effects and removal of IUCD usage - Pandey, Dhruvendra; Tiwari, Smriti (International Journal Of Community Medicine And Public Health, 2017)
Background: An effective contraception is the only way to stop this population explosion. There are too advantages and side effects associated with the IUCD, But most of side effects are effectively controlled by proper selection of clients and counseling process. Objective: To know the pattern of side effects and reason for removal among beneficiaries. Methods:A cross sectional study was conducted in 400 beneficiaries selected using systematic random sampling. Study sites included both urban and rural area. Data was entered and analyzed using MS excel sheet. Results: In this study maximum client 348 (87%) belonged to age group of 21 to 30 years. 47 (11.8%) clients were illiterate and 285 (71.3%) clients were unemployed/housewife. Most common side effect was pain with heavy bleeding in 30.6% clients, pain in 23.8% clients and pain with light spotting in 18.4% clients. Most common reasons for removal were pain with heavy bleeding in 42.6% clients while 10 (12.8%) clients removed due to husband’s insistence. Conclusions:After ICUD insertion 36.8% clients had side effect. Pain with heavy bleeding, pain with light spotting and only pain are the most common type of side effects. Removal of ICUD was 19.25%. Most common reason for removal was pain with heavy bleeding.